2014
DOI: 10.2169/internalmedicine.53.1407
|View full text |Cite
|
Sign up to set email alerts
|

An Inflammatory Polyp in the Colon Caused by the Migration of a Kirschner Wire Following Fixation of a Pelvic Fracture

Abstract: The migration of Kirschner wires (K-wires) is a rare complication. We herein present a case of an inflammatory polyp in the colon caused by the migration of a K-wire following fixation of a pelvic fracture. Surgery was carried out to remove the K-wire through an incision at the level of the left iliac bone. Simultaneous endoscopic clipping of the colonic wound was also performed. The patient's postoperative course was uneventful. Although very rare, migration of devices should be considered in patients with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…However, although migration of K-wires has been reported [4], migration into the gastrointestinal tract, especially with a pin passing across the sigmoid colon, is extremely rare. Intrapelvic migration of K-wires may lead to fatal complications due to injuries to the iliac artery, as well as perforation of the bladder, ureter, rectum, and colon, all of which have been previously reported [5][6][7][8][9]. Failure to remove these surgical devices, either because of lack of follow-up or because of delay due to a disease process, is associated with this complication.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, although migration of K-wires has been reported [4], migration into the gastrointestinal tract, especially with a pin passing across the sigmoid colon, is extremely rare. Intrapelvic migration of K-wires may lead to fatal complications due to injuries to the iliac artery, as well as perforation of the bladder, ureter, rectum, and colon, all of which have been previously reported [5][6][7][8][9]. Failure to remove these surgical devices, either because of lack of follow-up or because of delay due to a disease process, is associated with this complication.…”
Section: Discussionmentioning
confidence: 96%
“…Tamura et al [9] reported that chronic intramural stimulation by a migrated K-wire may cause the development of a colonic inflammatory granulation polyp, as can occur with silk sutures and vegetable seeds. In this case, the first CT examination did not show inflammation around the pin; however, the second CT examination showed slight inflammation although the cause was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] On the other hand, K-wire migration in hip and pelvic region is rarely seen, and a limited number of case reports have been published so far in the literature. For example, Tamura et al[ 10 ] and Fong et al[ 11 ] contributed to the literature with the case reports of K-wire migration in the 25th and 10th years after the pelvic fracture treatment. In the case report presented by Tamura et al,[ 10 ] they stated that K-wire migration caused the formation of inflammatory polyp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tamura et al[ 10 ] and Fong et al[ 11 ] contributed to the literature with the case reports of K-wire migration in the 25th and 10th years after the pelvic fracture treatment. In the case report presented by Tamura et al,[ 10 ] they stated that K-wire migration caused the formation of inflammatory polyp. Similar to these cases, Matsumoto et al[ 12 ] reported K-wire migration, which led to colon perforation 26 years after pelvic fracture surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Tamura et al [ 6 ] report a curious case of a migrant pin causing an inflammatory polyp in the colon 25 years after surgery for a pelvic fracture.…”
Section: Discussionmentioning
confidence: 99%